Complete genome sequence of Streptococcus troglodytae TKU31 isolated from the oral cavity of a chimpanzee (Pan troglodytes). (December 2016) - Okamoto, Masaaki; Naito, Mariko; Miyanohara, Mayu; Imai, Susumu; Nomura, Yoshiaki; Saito, Wataru; Momoi, Yasuko; Takada, Kazuko; Miyabe‐Nishiwaki, Takako; Tomonaga, Masaki; Hanada, Nobuhiro
ABSTRACT: Streptococcus troglodytae TKU31 was isolated from the oral cavity of a chimpanzee ( Pan troglodytes ) and was found to be the most closely related species of the mutans group streptococci to Streptococcus mutans . The complete sequence of TKU31 genome consists of a single circular chromosome that is 2, 097, 874 base pairs long and has a G + C content of 37.18%. It possesses 2082 coding sequences (CDSs), 65 tRNAs and five rRNA operons (15 rRNAs). Two clustered regularly interspaced short palindromic repeats, six insertion sequences and two predicted prophage elements were identified. The genome of TKU31 harbors some putative virulence associated genes, including gtfB, gtfC and gtfD genes encoding glucosyltransferase and gbpA, gbpB, gbpC and gbpD genes encoding glucan‐binding cell wall‐anchored protein. The deduced amino acid identity of the rhamnose‐glucose polysaccharide F gene ( rgpF ), which is one of the serotype determinants, is 91% identical with that of S. mutans LJ23 (serotype k ) strain. However, two other virulence‐associated genes cnm and cbm, which encode the collagen‐binding proteins, were not found in the TKU31 genome. The complete genome sequence of S. troglodytae TKU31 has been deposited at DDBJ/European Nucleotide Archive/GenBank under the accession no. AP014612.